Migration and HIV among Asian Populations: Social Work interventions - Sen, S; Aguilar, Jemel (Migrant Workers: Social Identity, Occupational Challenges and Health Practices, 2016)
Worldwide labor migration has transformed and reshaped various fields of government policy and professional practices. Labor migration is associated with the non-economic social phenomena that scholars have increasingly paid attention to in both sending and receiving destinations. For practitioners in the field of education, medicine, nursing, social work, mental health, public health, and other professional practices, the human face of labor migration migrant workers and their families daily challenges often reveals the human cost of migration behind the image of economic gain and benefits. Migrant workers and their families are facing vexing challenges ranging from basic needs to psychosocial well-being, despite who they are and where they come from. Traditional ways of thinking and knowing cannot address these challenges adequately; rather, established divisions of professions, systems, disciplines, and/or areas of practice might just be the factor that constrains the ability to clearly articulate compelling problems and adds an additional layer of complexity to problem solving. This book focuses on country policies and practices, and draws on theoretical ideas that provide the intellectual basis. In addition, it offers vivid examples of how migrant workers manage to work, pursue economic security, strive and adjust in new communities, define and negotiate self and identity, and seek health and well-being. While the book illuminates shared challenges and experiences for each group of migrant workers (i.e. low-skilled workers, internal migrants and other types of migrating laborers), it also synthesises the intersectionality across all migrant workers, as they remain committed to bettering the lives of their families and communities in their origin countries as well as new host countries and communities. This volume reflects the efforts of interdisciplinary research and collaboration
Keywords: dept.swk

Decolonizing Human Behavior in the Social Environment: A Reader for an Anti-Oppressive Approach - Aguilar, Jemel; Carpenter, Elisabeth Counselman (Cognella Academic Publishing, 2021)
Decolonizing Human Behavior in the Social Environment: A Reader for an Anti-Oppressive Approach challenges the socialization of preservice social workers by examining the complex features of individuals, families, groups, and societies and how they present themselves within the context of the multiple and simultaneous influences on behavior, cognitions, and emotions.This text is divided into three distinct units. Unit I development at the individual level and the influences that shape human behavior, including adverse childhood experiences, identity development through social media, resilience, and chronic illness. Unit II focuses on interpersonal dynamics with articles that explore grief theories, the transgender experience, intergenerational trauma, privilege, and more. Unit III examines structural social systems such as institutional racism, religious-based prejudice, and structural violence.Written to help social work students and professionals begin the process of decolonizing their education and practice, Decolonizing Human Behavior in the Social Environment is an essential and timely reader for courses and programs in social work. It is also an exemplary resource for practitioners at all levels.
Keywords: dept.swk

Everyone’s responsibility: Community partnerships and shared commitment for mental health promotion - Jung, Hyejin; Aguilar, Jemel P. (Social Work in Mental Health, 2016)
In this article, we use qualitative methods to understand the ways in which community involvement in a community-based mental health promotion conference encourages mental health care in an African-American community. We collected data through key informant interviews, focus groups, and participant observations at conference planning meetings and conferences, as well as archival documents related to the conference. We identify community partnerships and shared commitment as drivers of the outreach to people in the community, creators of a culturally relevant and supportive environment for mental health education, and, consequently, promoters of mental health care in the African-American community.
_eprint: https://doi.org/10.1080/15332985.2015.1130009
Keywords: African Americans; case studies; community partnerships; community-based programs; dept.swk; mental health and illness; mental health promotion

‘The mirage of action’: Exploring the social work professions’ perpetuation of white supremacy through ‘Well-Intentioned’ actions - Aguilar, Jemel P.; Counselman-Carpenter, Elisabeth (Advances in Social Work, 2021)
This autoethnographic study highlights complex strategies for maintaining white supremacy used by “well-intentioned” heterocentric white female social workers that are enacted under the guise of practicing anti-racism in social work practice settings, classroom environments, policy initiatives, and advocacy work. Using autoethnography was both unplanned and deliberate. Unplanned, we needed a research method that allows us to explore the untouchable subject of heterocentric white female social workers and deliberate in that we could use our experiences to break ground and establish white supremacy among heterocentric white female social workers that espouse anti-racist values as an area of study. We draw on education, anthropology, sociology, and other disciplines to name some of the ongoing challenges to dismantling racism, colonialist, and reformer narratives in social work, and identify strategies used by all white folx, but particularly heterocentric white female social workers to neutralize the suggestion or accusation of their acts as racism. We name three challenges to dismantling racism among heterocentric white female social workers: hiding behind the data, anti-racist book clubs, and crying and comfort. We conclude with further questions for those who hold power in the field and a reflection upon our own continued intersecting struggles with these concepts. © 2021 Authors,.
1 citations (Crossref) [2023-10-31]
Keywords: dept.swk; peer-reviewed

Best practices for assessing digital literacy and strengthening online teaching pedagogy of digitally immigrant stakeholders in higher education - Counselman-Carpenter, Elisabeth; Aguilar, Jemel P. (Lecture Notes in Networks and Systems, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: dept.swk

An ecological framework for understanding HIV- and AIDS-related stigma among Asian American and Pacific Islander men who have sex with men living in the USA - Sen, Soma; Aguilar, Jemel P.; Petty, Mac (Culture, Health and Sexuality, 2021)
Despite the fact that HIV- and AIDS-related stigma is consistently identified as an impediment to HIV prevention, a multilevel conceptualisation of HIV- and AIDS-related stigma continues to be poorly understood. The role of multilevel HIV- and AIDS-related stigma in the HIV prevention and intervention behaviours of Asian American and Pacific Islander who have sex with men in the USA is particularly overlooked. Psychology has contributed significantly to the identification of individual or interpersonal level factors influencing HIV- and AIDS-related stigma, while sociology has contributed to a more societal perspective. This dichotomy has led to the absence of a multilevel conceptual framework for analysing the HIV- or AIDS-related stigma experienced by Asian American and Pacific Islander who have sex with men in the USA. In this paper, we argue for need to develop such a model which is culturally grounded and bridges the individual, interpersonal and societal conceptualisations of stigma prominent in the social science literature. To that end, we use Bronfenbrenner’s ecological systems theory to explore the manifestation of HIV stigma at the micro, meso and macro levels and how these might impact on HIV testing and HIV service utilisation among Asian American and Pacific Islander men who have sex with men. We conclude by identifying some practice and research implications.
4 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85079445506
Keywords: Acquired Immunodeficiency Syndrome; Asian American; Asian Americans; HIV Infections; Homosexuality; Human immunodeficiency virus infection; Humans; Male; Sexual and Gender Minorities; United States; acquired immune deficiency syndrome; dept.swk; human; male; male homosexuality; peer-reviewed; sexual and gender minority

Appropriately Uncomfortable: A Conversation Among Three Colleagues About Structural Oppression Focusing on Racism and the Need for Action - Aguilar, Jemel; Smith, Carmela Fusciello; Tomczak, Stephen Monroe (Reflections: Narratives of Professional Helping, 2021)
In this reflection, three social work colleagues discuss three different perspectives on one statement about racism. We detail our emotionally challenging conversations about racism, microaggressions, and the meaning of social justice in social work to build a different bond and sense of understanding. We delve into how we understand each other, our differing viewpoints on the murders of Black people in American society such as George Floyd, and our perspectives on social workers’ relationships to social justice, racism, and social change in the context of the 2020 turmoil.
Number: 2
Keywords: dept.swk; higher education; oppression; peer-reviewed; racism; social work faculty

HIV Knowledge, Risk Behavior, Stigma, and Their Impact on HIV Testing among Asian American and Pacific Islanders: A Review of Literature - Sen, Soma; Nguyen, Hoang Dung; Kim, So Yung; Aguilar, Jemel (Social Work in Public Health, 2017)
Asian American and Pacific Islanders (AAPIs) are the fastest growing population in the United States with documented increases in HIV rates. AAPIs are as likely as other racial/ethnic groups to engage in HIV-related risk behaviors, while being concomitantly less likely to have been HIV tested. Testing is a critical step in HIV prevention. Research points to various barriers to HIV-related testing including HIV knowledge and attitude and stigma. However, these factors and their impact among AAPIs are poorly understood. Myths about this population's “model minority” status compound AAPIs' sociocultural factors including English language proficiency, access to healthcare, and a culture of “silence” that negatively influences HIV-related research. In this article, the authors review the scientific literature on knowledge, risk behavior, and stigma to document the current state of research. Based on the review the authors offer a set of research, policy, and practice recommendations for social workers and other service providers working with AAPIs.
_eprint: https://doi.org/10.1080/19371918.2016.1173612
Keywords: HIV and AAPI; Social epidemiology of HIV/AIDS; dept.swk; health disparities and HIV/AIDS

Exploring the Science of Conducting Surveys for Studying Men’s Sexual Assault Perpetration Behaviors - Aguilar, Jemel; Mahapatra, Neely; Busch-Armendariz, Noël; Dinitto, Diana M. (Journal of Aggression, Maltreatment & Trauma, 2016)
Focus groups were used to explore the most appropriate ways to conduct survey research about men’s relationships with women and their sexual assault behaviors that result in high response rates and decrease socially desirable answers. A racially diverse group of 24 English-speaking heterosexual men, aged 18 years or older, were recruited for participation in 3 focus groups. The men were asked to review a survey instrument used in a previous study and the results from that study. Analysis of the focus group transcripts indicates that the men responded to the survey instrument from 3 distinct perspectives: (a) perpetrators, (b) victims, and (c) respondents. From these perspectives, the men also commented on participant anonymity, survey construction and delivery method, question wording, and potential pitfalls in asking men about sexual assault.
_eprint: https://doi.org/10.1080/10926771.2015.1107171
Keywords: Engaging men; dept.swk; rape or sexual assault; survey methodology

Collaborating with transgender youth to educate healthcare trainees and professionals: randomized controlled trial of a didactic enhanced by brief videos - Martin, Andrés; Celentano, Jillian; Olezeski, Christy; Halloran, Justin; Penque, Brent; Aguilar, Jemel; Amsalem, Doron (BMC Public Health, 2022)
In collaboration with members of the transgender and gender diverse (TGD) community, we created a didactic resource about the unique needs of TGD youth.
0 citations (Crossref) [2023-10-31]
Keywords: Adolescents; Gender-diverse; Health; Health education; Mental health; Transgender; dept.mft; dept.swk; peer-reviewed

If Anti-Racism Is the Goal, Then Anti-Oppression Is How We Get There - Smith, Carmela Fusciello; Aguilar, Jemel P.; Kozu, Shuei; D'Angelo, Karen A.; Keenan, Elizabeth King; Tomczak, Stephen Monroe (Advances in Social Work, 2022)
Many schools of social work around the United States of America wrote anti-racism statements because of the recent murders of Black and Brown people. In this contribution, the authors describe a challenging and tense discussion of racism and anti-racism leading to a group process about oppression and anti-oppression in the social work profession. For some, the urgency to address racism led to tactics and strategies that got in the way of social workers engaging in anti-oppressive practices. While the structure of higher education often reinforces traditional hierarchies of power, the profession of social work calls us to promote our core values of social justice, integrity, and the importance of human relationships as we strive for an anti-oppressive future. Consequently, social work faculty may experience role conflict as we navigate these tensions. We believe it is important to harness and process such discomfort as we critically examine the power dynamics within our own department, and our own profession. This voluntary, ad hoc group, composed of a diverse group of faculty members, provides space for ongoing mutual aid, consciousness raising, appropriate discomfort, and accountability. If anti-racism is the goal, then anti-oppression is how we get there.
0 citations (Crossref) [2023-10-31] Number: 2
Keywords: White supremacy; dept.swk; peer-reviewed